If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-60=25(25-3x)
We move all terms to the left:
8x-60-(25(25-3x))=0
We add all the numbers together, and all the variables
8x-(25(-3x+25))-60=0
We calculate terms in parentheses: -(25(-3x+25)), so:We get rid of parentheses
25(-3x+25)
We multiply parentheses
-75x+625
Back to the equation:
-(-75x+625)
8x+75x-625-60=0
We add all the numbers together, and all the variables
83x-685=0
We move all terms containing x to the left, all other terms to the right
83x=685
x=685/83
x=8+21/83
| 6x=60−6x | | -10-n=-6(4n-6) | | -7n-22=-2(3n+4)-8 | | 3d-4=2+3d-0.5 | | (1/x-1)-1=0.01 | | (1/x-1)=0.01 | | -10y=y+14-5y | | 10=1/4(8y-12) | | 2.5(6x-2)=-3(x-8) | | 0=-40x-2x^2+12800 | | 11+4n=49 | | 0.5(b+3)=1 | | 1/3=8p | | (X+32)(3x-1)=0 | | 0.06y+0.03(4000-y)=156 | | -8-3w(w+13)=4(w+11)-7w | | 3x2+95x-32=0 | | (n-2)*180=135 | | 13=a-16 | | 2)3)n)n=54 | | 2.07=0.23p | | 3.5=5.5-0.4x | | 41.5=2p | | 3(5x-7)-2(9x-11)=4 | | M=6y+3 | | y/5+2(y+12)=3(y+y)-71 | | b=60+(20+7) | | 5y-(-2+4y)=5 | | ⅓y+¼=5/12 | | F=24-x/8x | | x²+14x-480=0 | | 2x^2-2x+4=12 |